Global Outsourcing in Indonesia: Opportunity and Challenge for The Labour - Puti Mayang Seruni; Ellydar Chaidir; Thamrin S (International Conference On Law And Social Sciences, 2024)
The topic of outsourcing is widely debated around the world. In Indonesia, outsourcing provides few guarantees for employment, work relationships, status, and worker protection. In Europe, it has been proven that outsourcing workers receive low wages and non-standard working hours. Even in France, there were many layoffs because companies decided to outsource. In China, outsourcing is currently used in the agricultural industry. Companies also use global outsourcing, such as France, which collects artificial intelligence data from workers in Madagascar via outsourcing. Companies often use global outsourcing to save costs and typically utilize workers from developing countries whose wages are low. This research aims to examine the opportunities and challenges faced by Indonesia regarding global outsourcing. The research uses a normative method that examines secondary data from statutory regulations, literature, and previous research results. The results will be presented descriptively. This research shows that outsourcing is profitable for companies because it can reduce job risks and obtain human resources at lower wages. Outsourcing also opens up employment opportunities, investment inflow, and transfer of knowledge and technology to advance industrialization in developing countries like Indonesia. However, Indonesia faces some challenges regarding legal substance, law enforcement, and legal culture. The current regulations in Indonesia need to be more robust to become the basis for outsourcing practices, both locally and globally.